An Intellectual Review of Muhammad Asif Mirza’s Ghazal - Shaheen, Shazia; Sahir, Muhammad Hassnain Sahir (sourcecoder, 2024)
Muhammad Asif Mirza (born: 21 May 1950) is a well known Poet and Critic. He is the Editor of an academic and literary magazine “Dastak Murree”. Muhammad Asif Mirza’s literary life is divided into three dimensions i.e. Poetry, Criticism and Editing. His two poetry collections “Sitara Hy Khak Per” and “Sada Pani Ki” have been published. Muhammad Asif Mirza's primary literary reference is poetry, and his primary creative reference in poetry is the “Ghazal”. Muhammad Asif Mirza is a prolific poet. Philosophy, mysticism, social contexts such as social inequality, social indifference and psychological conflict are the main themes of his Ghazal. Apart from this, simplicity, smoothness, meaningfulness, melody and musicality are the special characteristics of his poetry. His Ghazals have diverse themes. In this article, an attempt has been made to analyze his Ghazal in the light of different themes and characteristics.